USING BUSUU APPLICATION: ITS EFFECT ON STUDENTS’ VOCABULARY MASTERY AT SMP IT AL FITYAH PEKANBARU - Natasha, Harum; Mardiah, Diah (State Islamic University of Sultan Syarif Kasim Riau, 2025)
Vocabulary is a collection of words in a language that speakers understand and use for communication. However, many students have limited vocabulary knowledge, which negatively impacts their English proficiency. Common challenges include memorizing words, distinguishing meanings, and correct pronunciation. To address these issues, teachers need to implement effective vocabulary learning strategies. One application that supports vocabulary learning is Busuu, an online platform that provides language courses aligned with the Common European Framework of Reference for Languages (CEFR).This study aimed to examine the effect of using the Busuu application on students' vocabulary mastery in class VIII-A at SMP IT Al Fityah Pekanbaru. The research method used was pre-experimental with one-group pretest-posttest design. The sample consisted of 26 students selected through a convenience sampling technique. Data were collected through multiple-choice tests administered before and after treatment, then analyzed using SPSS 30 version. The results showed t-value of -3.257 and p-value of 0.003 (p < 0.05), leading to the rejection of HO and acceptance of Ha. In conclusion, the use of the Busuu application had a significant effect on students' vocabulary mastery.